2012
DOI: 10.3892/ijo.2012.1416
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid, a histone deacetylase inhibitor, enhances radiosensitivity in esophageal squamous cell carcinoma

Abstract: Abstract. Histone deacetylase (HDAC) inhibitors have been shown to enhance radiation response in various cancer cell lines. Valproic acid (VPA) has been used in clinical practice for the treatment of epilepsy and other seizure disorders and is also one of the most represented HDAC inhibitors. The aim of this study was to evaluate the radiosensitizing ability of VPA and its mechanisms in four esophageal squamous cell carcinoma (ESCC) cell lines (TE9, TE10, TE11 and TE14). VPA inhibited the viability of all ESCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…In addition, it is worth noting that a lessening of tremulous movements and a decrease in the number of seizures were found in three FCMTE patients after treatment with VPA and CBZ. These anti-epileptic drugs (AEDs) could raise the inhibitory neurotransmitter (e.g., GABA) concentrations by increasing GABA synthesis and decreasing GABA degradation, thus reducing the excitability of neurons and inhibiting seizures [28]. Here, this result is in line with the view that some AEDs (especially VBA and clonazepam) could improve the tremulous movements and lessen the number of seizures [4,7,8].…”
Section: Increased Alff In the Frontal Lobementioning
confidence: 76%
“…In addition, it is worth noting that a lessening of tremulous movements and a decrease in the number of seizures were found in three FCMTE patients after treatment with VPA and CBZ. These anti-epileptic drugs (AEDs) could raise the inhibitory neurotransmitter (e.g., GABA) concentrations by increasing GABA synthesis and decreasing GABA degradation, thus reducing the excitability of neurons and inhibiting seizures [28]. Here, this result is in line with the view that some AEDs (especially VBA and clonazepam) could improve the tremulous movements and lessen the number of seizures [4,7,8].…”
Section: Increased Alff In the Frontal Lobementioning
confidence: 76%
“…Therapeutic plasma concentrations used clinically for epilepsy treatment range from 50-100 µg/ml, which is equivalent to 0.3-0.6 mM. Therefore, 0.5 mM VPA is a clinically safe concentration (46) that we used in the present study based on our previous growth inhibition assay in which 0.5 mM VPA did not inhibit the growth of ESCC cells (36).…”
Section: Discussionmentioning
confidence: 98%
“…We recently showed that VPA enhanced the radiosensitizing effect by chromatin decondensation with histone hyperacetylation and downregulation of Rad51 (36). Various mechanisms are responsible for this VPA-mediated enhancement in radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been shown testing valproic acid on diff erent tumor cell lines other than SCLC. Masatoshi and co-authors showed a potential usefulness of NaVP in combination with radiotherapy for treating oesophageal cancer [18]. Nowak-Sliwinska with collaborators tested the eff ect of minimally invasive PDT (photodynamic therapy) that can potentially destroy the unwanted neoplastic tissue while sparing the neighbouring normal tissue.…”
Section: Discussionmentioning
confidence: 99%